P24 The forward myocardial creatine kinase reaction is increased in obesity. (21st March 2018) - Rayner, JJ; Clarke, W; Peterzan, MA; Rodgers, CT; Neubauer, S; Rider, OJ
Abstract : Background: Obesity is associated with impaired myocardial energetics (reduced phosphocreatine to adenosine triphosphate ratio (PCr/ATP)). However, LV systolic function is usually preserved, suggesting that the rate of ATP delivery to the contractile apparatus may be maintained. We hypothesised that the forward rate constant of the creatine kinase (CK) reaction would increase to compensate for the reduced substrate pool. Methods: 145 participants across a range of BMIs were recruited. All underwent CMR at 3T to determine LV geometry and function. Group A (75 individuals) underwent 31 P-MRS to assess PCr/ATP. The remaining 70 (group B) – 51 obese (BMI 36.1±5.3), and 19 normal weight (BMI 23.9±3.9) – underwent Triple Repetition time Saturation Transfer 31P-MRS to determine CK kf. Results: Body fat mass and PCr/ATP were negatively correlated in group A (r=−0.457, p<0.001). In group B, there were no differences between LV EDV, mass or LVEF between the groups (all p<0.05). CK forward rate constant (kf) was higher in obese participants than normal weight (CK Kf 0.20±0.12 s-1 vs 0.09±0.07 s-1; p=0.001). Myocardial CK kf increased in proportion to body fat (r=0.283, p=0.026). Conclusions: We studied the effect of obesity on CK kinetics in the human heart, and have demonstrated that, despite a fall in PCr/ATP with increasing body fat, the CK reaction rate is higher in obesity than in normal weight. This may reflect a compensatory increase in CK activity to maintain ATP delivery rates and attempt to preserve cardiac function despite a diminished substrate pool.